Compulsory vaccination of children: Rights of patients or interests of public health? - Draškić Marija (Anali Pravnog Fakulteta u Beogradu)
In recent years in Serbia - but also in recent decades in many other countries in the world - an intensive campaign of various social (most often Internet) groups against compulsory vaccination of children has taken place. Except for the pseudo-scientific study of Andrew Wakefield (1998), which has since been contested several times in serious scientific researches, as well as a few medical doctors in Serbia who referred to it, the whole of expert stakeholders, and epidemiologists in particular, has fiercely opposed the dangerous trend of parents renouncing compulsory vaccination of their children. This article aims to show that the consent to compulsory vaccination of children is not a matter of the right to autonomy in the field of medicine - which implies the freedom of every human being to decide on one's own life and body - but instead a matter of public health, which inevitably means of public interest as well, a matter which should be decided by competent professionals.